Progesterone/Estradiol Ratio as a Predictor in the ART Cycles with Premature Progesterone Elevation on the Day of hCG Trigger - M Mascarenhas; MSh Kamath; A Chandy; AT Kunjummen (JRI, 2015)
Background: The purpose of the study was to evaluate the role of Progesterone/ Estradiol (P4/E2) ratio as a predictive tool for clinical pregnancy in ART cycles with a premature progesterone rise of >1.5 ng/ml on the day of human chorionic gonadotropin (hCG) trigger. Methods: Retrospective analysis was done on 569 fresh embryo transfer cycles from January 2011 to December 2012 at the infertility unit of a tertiary care hospital. Age, BMI, number of cycles and number of clinical pregnancies have been considered. Results: The overall clinical pregnancy rate per embryo transfer was 42.8% (244/569). The clinical pregnancy rate in the 36 cycles with progesterone (P4) level >1.5 ng/ml was significantly lower than the 533 cycles with normal p4 ≤1.5 ng/ml (22.2% vs. 44.2%; p=0.0092). The 36 cycles with progesterone level >1.5 ng/ml were divided into subgroups of P4/E2 >1 (n=20) and P4/E2 ≤1 (n=16). The 20 cycles with P4/E2 >1 and P4 >1.5 ng/ml had a significantly lower pregnancy rate than the cycles with P4 ≤1.5 ng/ml (15% vs. 42.8%; p=0.0103). The 15 cycles with P4/E2 ≤1 and P4 >1.5 ng/ml had a similar pregnancy rate as the cycles with P4 ≤1.5 ng/ml. Conclusion: A premature progesterone elevation in ART cycles is possibly associated with lower clinical pregnancy rates; this adverse impact of elevated progesterone seems to be limited mainly to a subgroup with an elevated P4/E2 ratio >1.